Contemporary surgical management of fracatures & complications - Ilyas, Asif (New Delhi : Jaypee-Highligts Medical Publishers, 2013)
his two volume set is a complete guide to the surgical management of fractures and complications. Volume one discusses the upper extremity and spine and Volume two examines the pelvis and lower extremity. Each chapter discusses a different type of fracture, providing a step by step guide through history, clinical presentation, diagnostic testing, imaging, treatment and complications.
CONTENTS 1. Phalangeal fracture 2. Metacarpal fracturs and campometacapal fracture-dislocations 3. Carpal fracture and perilunate dislocation 4. Scaphoid fractures 5. Distal radius fracture y otros
Incluye índice
Keywords: HUESO -- lembs -- CIRUGÍA; CARTÍLAGO -- lembs -- CIRUGÍA; SURGICAL TECHNIQUES -- lembs